Clinical Dental Student Perception of Oral and Maxillofacial Surgery as a Specialty at Qassim University - Alotaibi Khalid Z; Altuwaijri Abdulrahman (Wolters Kluwer Medknow Publications, 2024)
The objective of the current research was to assess and gain insight into the perceptions held by dental students enrolled in the clinical program at Qassim University regarding the specialty of oral and maxillofacial surgery (OMFS). A survey-based cross-sectional study was carried out at the dental clinics of Qassim University, following approval from the Dental Research Center of the university. The study targeted a population consisting of 80 dental interns and undergraduate students (BDS) enrolled at Qassim University. From each academic year (third year to interns), a random selection of 20 students was made, ensuring representation from both male and female sections. Upon analyzing the data regarding the intern and class year of dental students, it was found that there were no statistically significant associations with regard to question 3: "What do you perceive as the most commonly performed procedure by oral and maxillofacial surgeons in practice?" (P = 0.759a). Among intern and dental students, a significant majority identified extraction of the third molars as the most frequent procedure carried out. The lowest percentage (70.4%) was reported among the intern classes, whereas the highest percentage (91.7%) was reported among the fourth-year students. The perceptions of dental students toward OMFS undergo changes during their undergraduate training. By gaining a deeper understanding of these perceptions, the academic faculty specialized in OMFS can enhance their ability to educate students and, in turn, strengthen the overall specialty.